1983
DOI: 10.1002/tea.3660200603
|View full text |Cite
|
Sign up to set email alerts
|

The effect of A teacher questioning strategy training program on teaching behavior, student achievement, and retention

Abstract: The use of questions in the classroom has been employed throughout the recorded history of teaching. One still hears the term “Socratic method” during discussions of questioning procedures. The use of teacher questions is presently viewed as a viable procedure for effective instruction. This study was conducted to investigate the feasibility of training teachers in the use of a questioning technique and the resultant effect upon student learning. The Post‐Test Only Control Group Design was used in randomly ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 4 publications
(1 reference statement)
0
5
0
Order By: Relevance
“…In addition, some researchers have indicated that retention and long-term outcomes of meaningful school materials can persist from one course to another, even over relatively extended intervals (Arzi et al, 1986). Other researchers have examined the relationship between the ability to retain certain learning skills and the time passed since acquiring these skills and their studies have shown similar results (Leonard, 1987;Leonard and Lowery, 1984;Otto and Schuck, 1983). …”
mentioning
confidence: 88%
“…In addition, some researchers have indicated that retention and long-term outcomes of meaningful school materials can persist from one course to another, even over relatively extended intervals (Arzi et al, 1986). Other researchers have examined the relationship between the ability to retain certain learning skills and the time passed since acquiring these skills and their studies have shown similar results (Leonard, 1987;Leonard and Lowery, 1984;Otto and Schuck, 1983). …”
mentioning
confidence: 88%
“…Accordingly, teachers' awareness of asking question strategies can be increased through various vocational development programs (Dantonio, 1990;Fairbain, 1987;Joyce & Showers, 1983). If, questioning typologies and cognitive demands that change accordingly and are embedded in the questions are presented to teachers on the basis of evidence through development programs, they will be motivated to their vocational development and adopt learner-centered instructional processes (Otto & Schuck, 1983;Sitko & Slemon, 1982). The main way for teachers to be motivated for vocational development programs is that they have the belief and awareness that the strategies they use can affect the cognitive states of the learners.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%
“…Paralleling the heightened concern about female performance in the classroom was a growing body of research underscoring the importance of the nature and frequency of classroom interaction in the educational achievement of students (Fennema & Peterson, 1978;Otto & Schuck, 1983;Redfield & Rousseau, 1981). Research investigations during the 1970s and 1980s emphasized the importance of direct instruction (Good, 1979), and male-female classroom interactions were analyzed through this new viewing glass.…”
Section: Gender Equity In Teacher-student Interactionmentioning
confidence: 98%